2014
DOI: 10.5958/2231-6701.2014.01195.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tillage, Mulching and Weed Management on Performance of Maize (Zea mays) in Karnataka

Abstract: A field experiment was conducted during kharif 2010 and 2011 to study the effect of tillage (conventional tillage, zero tillage and minimum tillage), mulching (no mulch and with mulch) and weed management practices (unweeded check, atrazine, and atrazine followed by 2, 4-D spray) on rainfed maize in Karnataka. Tillage, mulching and weed management practices significantly influenced the growth and yield of maize. Maize grain yield (5.91 t/ha) was significantly higher in conventional tillage system as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…This was owing to efficient utilization of available soil moisture, nutrients and solar energy at all the stages of crop growth and lower weed infestation as also reported by Choudhary et al, (2021). These results are in close conformity with the findings of Kumar and Angadi (2014). The different WMPs significantly affected the yield attributes and yield.…”
Section: Yield Attributes and Yieldsupporting
confidence: 88%
See 1 more Smart Citation
“…This was owing to efficient utilization of available soil moisture, nutrients and solar energy at all the stages of crop growth and lower weed infestation as also reported by Choudhary et al, (2021). These results are in close conformity with the findings of Kumar and Angadi (2014). The different WMPs significantly affected the yield attributes and yield.…”
Section: Yield Attributes and Yieldsupporting
confidence: 88%
“…Upasani et al (2017) also reported non-significant effect of tillage methods in maize -wheat system on dry-matter accumulation of weeds. The total dry-matter of weeds in maize crop was higher in ZT plots than MT and CT practices (Kumar and Angadi, 2014). Weed-management practices significantly influenced the weed dry weight at 30, 60 and 90 DAS (Table 2).…”
Section: Weed Dry Matter and Weed-control Efficiencymentioning
confidence: 99%
“…Treatments N 125 and N 150 in which 125 kg N ha -1 and 150 kg N ha -1 was applied were at par and superior to all other treatments. The higher DMA may be attributed to the fact that mulch helped in controlling the weeds and changed the microclimatic conditions near plant base leading to better growth of roots and more availability of nutrients that helped the plants to maintain higher photosynthetic efficiency and significantly higher number of leaves retained (Kumar and Angadi, 2014). This increase in DMA might be due to the fact that highest nitrogen level produced maximum plant height and number of leaves plant -1 as compared to its lower levels thus resulting in higher DMA Parija (2011) and Zhao et al, (2014).…”
Section: Resultsmentioning
confidence: 99%
“…Mulching practice was also proved effective for controlling the weeds reported by Kumar and Angadi, 2014. A perusal of data presented in Table 3 recorded under weedy check. The better expression of yield attributes in herbicide treated and hand weeded plots might be due to minimum crop weed competition during critical phases of crop growth either manually or chemically, exerts an important regulation function on complex processes of yield formation, due to better availability of growth inputs viz., water, space and nutrients.…”
Section: Resultsmentioning
confidence: 94%
“…Weed management practices brought down competition and created favourable micro-environment for better establishment, growth and development of maize crop.Weed control treatments also increased CGR, compared to weedy check that facilitated higher photosynthate production and translocation from source to sink, resulting in overall improvement in yield attributing traits and consequently the yields. Kumar and Angadi (2014), Samant et al 2015Teame et al 2017and Patel et al (2018) also observed significant effect of weed control in increasing yield of maize.…”
Section: Effect On Yields and Harvest Indexmentioning
confidence: 93%